2019
DOI: 10.1021/acsomega.8b03022
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Two Interfaces with Fluoroethylene Carbonate Electrolytes for High-Performance Li/LCO Batteries

Abstract: Various electrolytes have been reported to enhance the reversibility of Li-metal electrodes. However, for these electrolytes, concurrent and balanced control of Li-metal and positive electrode interfaces is a critical step toward fabrication of high-performance Li-metal batteries. Here, we report the tuning of Li-metal and lithium cobalt oxide (LCO) interfaces with fluoroethylene carbonate (FEC)-containing electrolytes to achieve high cycling stability of Li/LCO batteries. Reversibility of the Li-metal electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…To characterize the SEI composition, X‐ray photoelectron spectroscopy (XPS) of the Li metal surfaces was conducted after 10 cycles of galvanostatic plating/stripping. In the O 1s spectra in Figure 4e, the COC bond peaks, which are related to the DME decomposition, [ 31 ] decreased evidently when increasing the LiNO 3 ratio. Since the solvent coordination on Li + solvation reduced with the NO 3 − addition, the direct contact of DME with Li metal was repressed, then its reductive decomposition was effectively suppressed throughout cycles.…”
Section: Resultsmentioning
confidence: 99%
“…To characterize the SEI composition, X‐ray photoelectron spectroscopy (XPS) of the Li metal surfaces was conducted after 10 cycles of galvanostatic plating/stripping. In the O 1s spectra in Figure 4e, the COC bond peaks, which are related to the DME decomposition, [ 31 ] decreased evidently when increasing the LiNO 3 ratio. Since the solvent coordination on Li + solvation reduced with the NO 3 − addition, the direct contact of DME with Li metal was repressed, then its reductive decomposition was effectively suppressed throughout cycles.…”
Section: Resultsmentioning
confidence: 99%
“…The difference in the permeability of the binder layer to the electrolyte could also affect the onset potential of FEC decomposition. 76 Indeed, FEC has a large permittivity (ε r = 110) 77 and a highly charged binder layer such as for pH 6 could facilitate the passage of the electrolyte through this layer because of the dissociation of the lithium carboxylate groups. As a matter of fact, the ionization of the COO − −Li + bonds must facilitate the separation of the polymer chains via the electrostatic repulsion between the neighboring carboxylates and the swelling of the polymer layer by the electrolyte.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Furthermore, the use of suitable additives remarkably enhanced the electrode passivation behavior, leading to promising cell performances. Indeed, literature works have shown that vinylene carbonate (VC), fluoroethylene carbonate (FEC), and lithium nitrate (LiNO 3 ) may improve the SEI between anode and electrolyte. In particular, it is widely demonstrated that LiNO 3 ‐containing electrolytes may form a uniform and stable anode passivation layer containing both organic ( e.g ., ROLi and ROCO 2 Li) and inorganic ( e.g ., Li x NO y , Li 3 N, and Li 2 O) species, which can mitigate the parasitic reactions in the cell and limit the lithium dendrite growth .…”
Section: Introductionmentioning
confidence: 99%